Observation of interspecies 6Li- 133Cs feshbach resonances - Repp, Marc; Pires, Rico; Ulmanis, Juris; Heck, Robert; Kuhnle, Eva; Weidemüller, Matthias; Tiemann, E. (Physical review. A, Atomic, molecular, and optical physics, 2013)
We report on the observation of 19 interspecies Feshbach resonances in an optically trapped ultracold Bose-Fermi mixture of 133Cs and 6Li in the two energetically lowest spin states. We assign the resonances to s- and p-wave molecular channels by a coupled-channels calculation, resulting in an accurate determination of LiCs ground-state potentials. Fits of the resonance position based on the undressed asymptotic bound state model do not provide the same level of accuracy as the coupled-channels calculation. Several broad s-wave resonances provide prospects to create fermionic LiCs molecules with a large dipole moment via Feshbach association followed by stimulated Raman passage. Two of the s-wave resonances overlap with a zero crossing of the Cs scattering length, which offers prospects for the investigation of polarons in an ultracold Li-Cs mixture.
Im Text sind "6" und "133" hochgestellt
Gesehen am 03.01.2022